Development of an innovative technology for wood delignification with eutectic solvents - Soares, Belinda Isabel Gomes (2021)
The goal of this work was to study the use of Eutectic Solvents (ESs) for wood fractionation aiming at their application on pulping processes, in the biorefinery framework. To achieve this purpose, fundamental studies were performed to better understand the solubility of lignin monomer model compounds (syringaldehyde and syringic, vanillic and ferulic acids) and technical lignins (kraft and organosolv) in ESs and their aqueous solutions. Particularly, aqueous solutions of propionic acid:urea (2:1) at 50 or 75 wt % of concentration and 353.15 K improved lignin solubility by two orders of magnitude in comparison to water and conventional lignin solvents [solubility enhancement of (228.3 ± 8.2)- and (474.7 ± 2.7)-fold for kraft and organosolv lignin, respectively]. Furthermore, maximum solubilization of lignin monomer model compounds was achieved using ethylene glycol:tetrabutylphosphonium chloride (2:1) aqueous solutions at 50 or 75 wt % of concentration and 323.15 K [(34.9 ± 6.7)-, (116.6 ± 1.6)-, (58.6 ± 0.4)- and (202.5 ± 16.9)-fold, respectively]. It should be highlighted the fundamental role of water, which allows a hydrotropic effect on lignin (and their monomers) solubility in these ESs aqueous solutions. The best ESs to enhance the solubility of lignin in water was used to develop a new wood delignification process. Therefore, delignification of Eucalyptus globulus wood catalyzed by mineral or organic acids in ESs aqueous solutions was studied. The results obtained confirmed that the wood delignification using ESs aqueous solutions requires the addition of acid catalyst in order to enhance lignin removal. Two different ESs aqueous systems were identified as the best to delignify E. globulus wood under mild conditions: (i) the 50 wt % aqueous solution of propionic acid:urea (2:1) in the presence of 25 wt % of p-toluenesulfonic acid as catalyst (8 h, 363.15 K and atmospheric pressure). This system led to the production of a solid fraction yield of 59.50 ± 0.51 wt %, containing a residual Klason lignin of 3.86 ± 0.10 wt % with preserved cellulose fibers, when compared to conventional E. globulus kraft pulp; and (ii) the 50 wt % aqueous solution of ternary-ESs mixture (sodium p-toluenesulfonate:p-toluenesulfonic acid:choline chloride) at optimal molar ratio of (0.393:0.376:0.232) that allowed producing 46.60 ± 2.70 wt % of solid fraction yield, containing a residual Klason lignin of 2.74 ± 0.08 wt % under milder conditions (3 h, 363.15 K and atmospheric pressure). Moreover, the chemical structural analysis of both isolated lignins revealed that fewer transformations are induced by these systems, when compared to E. globulus kraft, and other ESs reported in literature. Finally, promising preliminary results show the feasibility for scaling the ES wood delignification process using both ESs.